Neuro-axonal injury in COVID-19: the role of systemic inflammation and SARS-CoV-2 specific immune response. (March 2022) - Hirzel, Cédric; Grandgirard, Denis; Surial, Bernard; Wider, Manon F.; Leppert, David; Kuhle, Jens; Walti, Laura N.; Schefold, Joerg C.; Spinetti, Thibaud; Suter-Riniker, Franziska; Dijkman, Ronald; Leib, Stephen L.
Background: In coronavirus disease-2019 (COVID-19) patients, there is increasing evidence of neuronal injury by the means of elevated serum neurofilament light chain (sNfL) levels. However, the role of systemic inflammation and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific immune response with regard to neuronal injury has not yet been investigated. Methods: In a prospective cohort study, we recruited patients with mild–moderate ( n  = 39) and severe ( n  = 14) COVID-19 and measured sNfL levels, cytokine concentrations, SARS-CoV-2-specific antibodies including neutralizing antibody titers, and cell-mediated immune responses at enrollment and at 28(±7) days. We explored the association of neuro-axonal injury as by the means of sNfL measurements with disease severity, cytokine levels, and virus-specific immune responses. Results: sNfL levels, as an indicator for neuronal injury, were higher at enrollment and increased during follow-up in severely ill patients, whereas during mild–moderate COVID-19, sNfL levels remained unchanged. Severe COVID-19 was associated with increased concentrations of cytokines assessed [interleukin (IL)-6, IL-8, interleukin-1 beta (IL-1β), and tumor necrosis factor-alpha (TNF-α)], higher anti-spike IgG and anti-nucleocapsid IgG concentrations, and increased neutralizing antibody titers compared with mild–moderate disease. Patients with more severe disease had higher counts of defined SARS-CoV-2-specific T cells. Increases in sNfL concentrations from baseline to day 28(±7) positively correlated with anti-spike protein IgG antibody levels and with titers of neutralizing antibodies. Conclusion: Severe COVID-19 is associated with increased serum concentration of cytokines and subsequent neuronal injury as reflected by increased levels of sNfL. Patients with more severe disease developed higher neutralizing antibody titers and higher counts of SARS-CoV-2-specific T cells during the course of COVID-19 disease. Mounting a pronounced virus-specific humoral and cell-mediated immune response upon SARS-CoV-2 infection did not protect from neuro-axonal damage as by the means of sNfL levels.